The Effect of Automation of Banking Services on Customer Satisfaction - Halder, Sagar; Albino, Michael Generalo; Peralta, Gene Abelon (The Asian Journal of Technology Management (AJTM), 2022)
Abstract. Automated banking is one of the key services used by banks to facilitate the delivery of services that meet consumer expectations, thus boosting the country’s economy. Major technological advancements have been witnessed in the banking industry due to the introduction of international standards in the operational norms of banking geared towards the betterment of client service quality. The aim of this research was to assess the effects of automation of banking services on customer satisfaction for different private banks in Khulna city. The study adopted a case study research design. Data was collected using questionnaires. The total reliability of the questionnaire, measured using a Cronbach's alpha coefficient, was 0.897. The sample size was 100 respondents. Data were analyzed using descriptive and inferential statistics using Statistical Package of Social Sciences (SPSS) software, version 20.0. Findings were presented in the form of tabulations (percentages, mean and standard deviation). From the findings, the automation of banking services such as mobile banking usage, internet banking usage, and automated teller machine usage was found to have a significant effect on customer satisfaction.Keywords:  Mobile banking, internet banking, automated teller machine, customer satisfaction